VIEWED FROM CREDIT RISK CREDIT AND TYPE OF INTEREST RATE GUARANTEES Case Study-BKK On PD.BPR Karangreja Purbalingga - Nugroho, Afandi Setyo; Nursasmita., Akuntan, Drs. H. Irfan (Accounting, 2009)
This study aims to determine whether there is any difference in the bank´s credit risk BPR-BKK Karangreja PurbalinggaDitinjau of interest rate differentials credit and credit guarantees. Data collection techniques used were interviews and documentation. Data analysis techniques used to answer the first problem is to analyze the differences between the two average, which is to analyze whether there are differences in credit risk viewed from different interest rates. While the data analysis techniques used to answer the second problem is by using analysis of variance, which tested whether there are differences in credit risk viewed from a different warranty. Based on the results of data analysis can be concluded that there are differences in credit risk viewed from different interest rates. Meanwhile, to guarantee there is no difference seen the credit risk of loan collateral types PD.BPR Karangreja Purbalingga-BKK. From data analysis it can be seen there is no difference between the credit risk of loans with collateral BPKB, land certificates, and SK. PNS. Key words: credit risk, interest rate, credit guarantees.